2003
DOI: 10.3748/wjg.v9.i11.2480
|View full text |Cite
|
Sign up to set email alerts
|

Oxymatrine therapy for chronic hepatitis B: A randomized double-blind and placebo-controlled multi-center trial

Abstract: AIM:To evaluate the efficacy and safety of capsule oxymatrine in the treatment of chronic hepatitis B. METHODS:A randomised double-blind and placebocontrolled multicenter trial was conducted. Injection of oxymatrine was used as positive-control drug. A total of 216 patients with chronic hepatitis B entered the study for 24 weeks, of them 108 received capsule oxymatrine, 36 received injection of oxymatrine, and 72 received placebo. After and before the treatment, clinical symptoms, liver function, serum hepatit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 38 publications
(48 reference statements)
2
50
0
Order By: Relevance
“…Antiviral agents working through this mechanism inhibit the replication of not only wild-type HBV, but also drugresistant mutants. Clinical studies have shown that injection of OMTR (0.4 g/day for 6 months) in CHB patients caused over 40% of the patients to become negative for HBV DNA (12), and viral-load measurement showed that OMTR injection (0.4 g/day for 3 months) decreased the HBV viral load by about 2 log units on average (4). The anti-HBV effect of OMTR in patients basically agrees with that described here in HepG2.2.15 cells, but with higher efficacy, because the HBV viral-load test in the clinical setting measures the de novo synthesized viruses in blood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antiviral agents working through this mechanism inhibit the replication of not only wild-type HBV, but also drugresistant mutants. Clinical studies have shown that injection of OMTR (0.4 g/day for 6 months) in CHB patients caused over 40% of the patients to become negative for HBV DNA (12), and viral-load measurement showed that OMTR injection (0.4 g/day for 3 months) decreased the HBV viral load by about 2 log units on average (4). The anti-HBV effect of OMTR in patients basically agrees with that described here in HepG2.2.15 cells, but with higher efficacy, because the HBV viral-load test in the clinical setting measures the de novo synthesized viruses in blood.…”
Section: Discussionmentioning
confidence: 99%
“…2b). The results were of great interest to us, because the compound has been used to treat viral hepatitis in China since the 1990s (3,4,12,24). However, its anti-HBV mechanism remains unclear.…”
Section: Hostmentioning
confidence: 99%
“…It has been used to treat chronic hepatitis B patients in China for decades with confirmed safety [14]. Recent evidence has shown that oxymatrine possesses a wide variety of pharmacological effects, including anti-inflammatory, anti-apoptosis, anti-tumor, anti-hepatic fibrosis, and anti-arrhythmic functions [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Oxymatrine (Figure 6), an alkaloid from the herb Sophora alopecuraides L., was reported to exhibit anti-HBV effect in HBV transgenic mice [25,26] and patients with chronic HBV infection [27]. The antiviral mechanisms may be interfering with the reverse transcription process from pgRNA to DNA by destabilizing Hsc70 mRNA, and then inhibiting the replication of HBV [28].…”
Section: Heat Stress Cognate 70 (Hsc70)mentioning
confidence: 99%